Anthropocene Antarctica: Approaches, issues and debates - Elizabeth Leane; Jeffrey McGee (2019)
The Antarctic is a region that traditionally occupied the remote reaches of the geographical imagination. In the Anthropocene, however, the ‘frozen continent’ has become central to the planet’s present and future. Even as ice cores taken from its interior reveal the deep environmental history of the planet, warming ocean currents are ominously destabilising the glaciers around its edges. The continent contains over ninety per cent of the world’s ice, with the potential to raise sea levels by nearly sixty metres, if it were all to melt. While such a wholesale melt of the Antarctic ice sheet is not imminent, estimates (based on a business-as-usual greenhouse gas emissions scenario) indicate the continent’s ice could contribute over a metre of sea-level rise by the end of this century and over fifteen metres by 2500 (DeConto & Pollard 2016). And warming global average temperature – along with associated effects, such as ocean acidification and species migration – are only some the hallmarks of the global-scale threats to the region’s environment arising from activities remote from the continent itself. Marine microplastics pollution, possibly originating from outside the region, has been found in Antarctic waters (Waller et al. 2017). The thinning of the ozone layer in the atmosphere above the continent, identified by Antarctic scientists in the 1980s, has begun to abate due to international action to reduce the use of ozone-depleting gases, but recovery of ozone concentration to 1980s levels is not expected until the second half of this century (World Meteorological Organization 2018, p. 3). For many decades framed as a ‘last wilderness’, Antarctica is now increasingly understood as an environment irrevocably altered by remote human action and one that will irrevocably change the course of human lives all over the globe.